Kotekstualisasi Fikih Golongan Penerima Zakat (Asnaf Tsamaniyah) Zakat dan Relevansinya dengan Penanggulangan Kemiskinan di Indonesian - Rahmad Hakim (Proceedings of Annual Conference for Muslim Scholars, 2018)
This paper aims to conduct an in-depth analysis related to the contextualization of zakat distribution in Indonesia. The discussion begins with the effort of contectualization of the recipient group of zakat (aṣnāf ṡamaniyah) that includes; fakir, miskin, gharim, muallaf, fi sabilillah, ibnu sabil, amil dan riqab. Given that the gap has not shifted significantly since since December 2015, the gap in the income gap ratio only ranges from 0.41-0.43 so that the priority of zakat distribution in Indonesia is for fakir and miskin. Based on the research, it can be concluded that efforts to strengthen the distribution of zakat through the contextualization of eight categories of recipients of zakat (aṣnāf ṡamaniyah); with this effort is expected zakah institutions such BAZ and LAZ have those specialization. For example Zaka Institution A specializing on ​​programs for productive enterprises, where Zakah institution B specializing on providing scholarships and trainings program. On the other hand, Zakah institution C specializing on the construction of facilities and infrastructure program, and so forth. The existence of synergy and cooperation to reinforce each institution is needed nowadays. On the other hand, poverty reduction can work effectively if each party can play its own roles; where the individual understands that improving skills and work ethics are important to alleviate them from poverty, the role of wealthy relatives, communities and governments is important to encourage them to prosper by providing material assistance for their lives. In this context, the role of established and trusted zakat institutions is needed.